Inovação e sustentabilidade: análise do programa de pesquisa, desenvolvimento e inovação (PROPDI) do setor elétrico brasileiro - Jonas Antunes da Costa (2023)
In the global energy sector, the current scenario is one of transition to a future energy matrix more aligned with the three pillars of sustainability, economic, social and environmental, which aim to guarantee the development of the planet. The electricity sector is strategic, given its importance in the global energy matrix, one of the reasons why it has been seeking to develop innovative projects that are more attentive to the principles of sustainability. In this context, this research had the general objective of identifying the main management problems of the Research, Development and Innovation Program (PROPDI) of the Brazilian electricity sector, analyzing how these problems are being addressed in the new Normative Resolution of the National Electric Energy Agency (Aneel ) nº 1.045/2023, and even if the guidelines and procedures presented in the Resolution are in line with the basic principles of sustainability, which the current scenario of energy transition demands. The study reviewed national and international literature in order to identify the latest on sustainable innovation in the electricity sector. The methodology, in addition to the bibliographic nature, was also a documental study, as it made a technical assessment of what is provided in Aneel Resolution nº 1.045/2022. The results of the study indicated that the new procedures defined for the Innovation Program (PDI), coordinated by Aneel, are promising for a better management of innovation projects in the Brazilian electricity sector, since it contemplates the sector's claims, especially with respect to greater transparency, flexibility and control of the program. However, from the point of view of sustainability, the content of Aneel Resolution nº 1.045/2022 shows an imbalance in the treatment given to the three pillars of sustainability, with a preponderance of indicators from the economic pillar, also called the governance pillar, in relation to the social pillars and environmental. In the final considerations, there is an analysis of the feasibility of investing in projects that conform to the basic pillars of sustainability. Keywords: innovation; sustainability; Research and Development; innovation projects; electric sector; Aneel Normative Resolution nº 1.045/2022.